PENINGKATAN PRESTASI BELAJAR SEJARAH DENGAN SELF-REGULATED LEARNING PADA SISWA KELAS XI IPS DI SMA NEGERI 1 BANYUDONO TAHUN PELAJARAN 2012/2013 - Fajarwati, Marchela Siwi (Candi, 2013)
The Aims of this research are: 1) To analyze the relationship self-regulated learning with achievement of studying history students class XI IPS at SMA Negeri 1 Banyudono. 2) To analyze the relationship of the perception of students in the history teaching with achievement of studying history students class XI IPS SMA Negeri 1 Banyudono. The result of regression analysis acquired the equality of regression line Y= 67,530 + 0,093X1 + 0,075X2. The equality indicated that the achievement of studying history was influenced by self-regulated learning and the perception of students in the history teaching. The conclusion were taken were: 1) Self- regulated learning related positively with the achievement of studying history students class XI IPS at SMA Negeri 1 Banyudono, could be accepted. It based on double linier regression analysis ( test t ) known that t count > t table, that was 3,603 > 2,000 and score of significance < 0,05, that was 0,001 with relative contribution was 66% and effective one was 11, 02%. 2) The perception of students in the history teaching related positively with the achievement of studying history students class XI IPS at SMA Negeri 1 Banyudono, could be accepted. It based on double linier regression analysis ( test t ) known that t count > t table, that was 2,157 > 2,000 and score of significance < 0,05, that was 0,034 with relative contribution was 34% and effective one was 5,6%. 3) Self- regulated learning and the perception of students in the history teaching related positively with the achievement of studying history students class XI IPS at SMA Negeri 1 Banyudono in togetherness, could be accepted. It based on double linier regression variant analysis ( test T ) known that T count > F table, that was 8,602 > 3,150 and score of significance was < 0,05, that was 0,000. The coefficient of determination ( R2 ) was 0,167 indicated that the extent of related of self-regulated learning and the perception of students in teaching history with the achievement of studying history was 16, 7%, whereas the remains were influenced by other variables. Keywords: Self- Regulated Learning, Perception Of Students In The History Teaching, and Achievement Of Studying